Проблеми кризи та безробіття в Україні - Гончаров, В. В.; Омельяненко, О. П.; Гольда, А. В. (Ways to Improve Construction Efficiency, 2012)
The analysis of the general economic and specific causes of the crisis in Ukraine, its impact on the dynamics and structure of unemployment at this stage of the reproductive process.